2011
DOI: 10.3354/meps09246
|View full text |Cite
|
Sign up to set email alerts
|

Microgeographical population structure and adaptation in Atlantic cod Gadus morhua: spatio-temporal insights from gene-associated DNA markers

Abstract: Recent technical advances have stimulated studies on spatial scales of adaptive genetic variation in marine fishes. However, very few studies have combined spatial and temporal sampling to investigate adaptive genetic structuring at local and microgeographical scales, i.e. scales at which neutral genetic markers have typically revealed very limited levels of population structure. In the present study we analyzed 92 gene-associated single-nucleotide polymorphism (SNP) markers in Atlantic cod Gadus morhua from s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 78 publications
2
28
1
Order By: Relevance
“…Intermediate migration patterns, often observed in hybrids (Moore et al, 2010;Pujolar et al, 2014), may also result in underrepresentation of hybrids in our samples. This contrasts with evidence of adaptation in cod that is either temporally unstable (Poulsen et al, 2011;Therkildsen, Hemmer-Hansen, Als, et al, 2013;Therkildsen, Hemmer-Hansen, Hedeholm, et al, 2013) or if temporally stable, it is linked to chromosomal rearrangements (e.g., inversions) as seen in the differentiation between migratory and stationary cod ecotypes (Berg et al, 2016;Kirubakaran et al, 2016) shown to be present on both sides of the Atlantic Ocean (Berg et al, 2017). This contrasts with evidence of adaptation in cod that is either temporally unstable (Poulsen et al, 2011;Therkildsen, Hemmer-Hansen, Als, et al, 2013;Therkildsen, Hemmer-Hansen, Hedeholm, et al, 2013) or if temporally stable, it is linked to chromosomal rearrangements (e.g., inversions) as seen in the differentiation between migratory and stationary cod ecotypes (Berg et al, 2016;Kirubakaran et al, 2016) shown to be present on both sides of the Atlantic Ocean (Berg et al, 2017).…”
Section: Both Recruitment and Abundance Of Herring In The Northwestcontrasting
confidence: 77%
See 1 more Smart Citation
“…Intermediate migration patterns, often observed in hybrids (Moore et al, 2010;Pujolar et al, 2014), may also result in underrepresentation of hybrids in our samples. This contrasts with evidence of adaptation in cod that is either temporally unstable (Poulsen et al, 2011;Therkildsen, Hemmer-Hansen, Als, et al, 2013;Therkildsen, Hemmer-Hansen, Hedeholm, et al, 2013) or if temporally stable, it is linked to chromosomal rearrangements (e.g., inversions) as seen in the differentiation between migratory and stationary cod ecotypes (Berg et al, 2016;Kirubakaran et al, 2016) shown to be present on both sides of the Atlantic Ocean (Berg et al, 2017). This contrasts with evidence of adaptation in cod that is either temporally unstable (Poulsen et al, 2011;Therkildsen, Hemmer-Hansen, Als, et al, 2013;Therkildsen, Hemmer-Hansen, Hedeholm, et al, 2013) or if temporally stable, it is linked to chromosomal rearrangements (e.g., inversions) as seen in the differentiation between migratory and stationary cod ecotypes (Berg et al, 2016;Kirubakaran et al, 2016) shown to be present on both sides of the Atlantic Ocean (Berg et al, 2017).…”
Section: Both Recruitment and Abundance Of Herring In The Northwestcontrasting
confidence: 77%
“…Adaptive variation may, however, shift due to fluctuating selective pressures, with little repeatability over time and hence little predictive value (Poulsen, Hemmer-Hansen, Loeschcke, Carvalho, & Nielsen, 2011;Therkildsen, Hemmer-Hansen, Als, et al, 2013;Therkildsen, Hemmer-Hansen, Hedeholm, et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Nielsen et al 2006, Skarstein et al 2007) and single nucleotide polymorphisms (SNPs; e.g. Moen et al 2008, Nielsen et al 2009a, Poulsen et al 2011, the important role of selected markers to reveal adaptive population divergence on ecological time scales seems no longer disputable (see also Waples & Gagiotti 2006, Helyar et al 2011, and reviews by Kirk &Freeland 2011 andSalmenkova 2011). The power of assigning individuals to populations of origin is also strengthened by exploiting loci under selection (Nielsen et al 2009b).…”
Section: Introductionmentioning
confidence: 99%
“…A heterogeneous environment can restrict gene flow and increase the opportunity for local adaptation (Kawecki and Ebert 2004;Larmuseau et al 2009a;Hohenlohe et al 2010;Poulsen et al 2011;Hice et al 2012;Limborg et al 2012;Berg et al 2015). When immigrants to a population perform more poorly compared to locally adapted residents, natural selection will form a barrier against gene flow that can promote further reproductive isolation.…”
mentioning
confidence: 99%